OUR EXPERIENCES WITH PLATYSMA MYOCUTANEOUS FLAP IN HEAD AND NECK RECONSTRUCTION - Cherian, T; Kurien, J; Vijaykumar, D K; Chittoria, R (Indian Journal of Plastic Surgery, 2000)
In eighty-five patients under this study ipsilateral platysma myocutaneous flaps were used. The various regions reconstructed were tongue (47%), buccal mucosa (27%), floor of mouth (14%), lower alveolus (4%), maxilla (4%), lower lip (2%) and face (2%). Partial flap necrosis was noticed in 17 cases (20%), complete flap necrosis in six cases (7%) and wound infection in three cases ( 3%). The platysma myocutaneous flap provides a less bulky and versatile flap for head and neck reconstruction.
Keywords: Head and neck reconstruction; Platysma; Myocutaneous flap